A structurally simple linear conjugated polymer toward practical application of organic solar cells. Issue 11 (14th October 2022) - Yin, Bingyan; Pang, Shuting; Chen, Zhili; Deng, Wanyuan; Liu, Zhitian; Duan, Chunhui; Huang, Fei; Cao, Yong
Abstract : PTTzF, a linear conjugated polymer donor featuring simple synthesis, high device efficiency, outstanding batch reproducibility, and good universality with different acceptors is a promising candidate for practical application of organic solar cells. Abstract : The commercialization of organic solar cells (OSCs) requires the realization of highly efficient devices from low-cost polymer donors with excellent batch-to-batch reproducibility and universality matching with different electron acceptors. Herein, PTTzF, a structurally simple linear conjugated polymer with a donor–acceptor alternating structure toward practical application is developed. The polymer can be synthesized within ten steps of the reaction from cheap raw chemicals, making it much more easily accessible than the existing high-performance polymer donors. Meanwhile, the polymer is able to produce over 18% efficiency in OSCs, which renders it one of the most efficient polymer donors reported to date. Besides, PTTzF exhibits excellent batch-to-batch reproducibility benefiting from the good control of molecular weights within a certain range through rational selection of the comonomer with appropriate polymerization reactivity, which is beneficial for future scale-up synthesis from laboratory to factory. The polymer also exhibits good universality with different acceptors, including fullerene derivatives, A–D–A and A–DA'D–A type non-fullerene acceptors, which offer a capability to match with the currently existing and future potential acceptors. The merits of low cost, high efficiency, excellent reproducibility, and good universality make PTTzF an ideal polymer donor for real world applications of OSCs.